Planning profitable tours for field sales forces: A unified view on sales analytics and mathematical optimization. (December 2021) - Meyer, Anne; Glock, Katharina; Radaschewski, Frank
Highlights: This paper jointly considers sales analytics and optimization for the day-to-day operations of field sales forces. Different approaches for estimating customer profitability are translated into team orienteering problems. When customers response can be reliably predicted, this information consistently improves operational plans but a large and detailed historical data base is necessary. In contrast, simple methods to identify the most important customers or to build rough classes of customers produce very good results compared to a relatively low data acquisition effort. Abstract: A key task of sales representatives in operational planning is to select the most profitable customers to visit within the next few days. A strongly varying set of scoring methods predicting or approximating the expected response exists for this customer selection phase. However, in the case of field sales forces, the final customer selection is strongly interrelated with the tour planning decisions. To this end, we formalize variants of the profitable sales representatives tour problem as a multi-period team orienteering problem, thereby providing a unified view on the customer scoring and the tour planning phase. In an extensive computational study on real-world instances from the retail industry, we systematically examine the impact of the aggregation level and the content of information provided by a scoring method and the sensitivity of the proposed models concerning prediction errors. We show that the selection of a customer scoring and tour planning variant depends on the available data. Furthermore, we work out where to put in effort for the data acquisition and scoring phase to get better operational tours.